The Reality Of The Application Of Takaful Insurance In Algeria And Its Prospects Under Executive Decree No. 21-81 - Talhi, Kaouther (جامعة الوادي - University of Eloued, 2021)
This study aims to determine the reality of the application of Takaful insurance in Algeria, and the prospects for its application in the future in light of the Algerian legislator’s issuance of Executive Decree no. 21-81, specifying the conditions and modalities for practicing Takaful insurance, which is the first explicit step towards adopting the Takaful insurance industry in Algeria. This study concluded that “Salama Assurances Algérie” has partially applied the Takaful insurance mechanism previously, despite the lack of the necessary legal environment for it. This matter was resolved by the Algerian legislator through the issuance of Executive Decree no. 21-81, that has been widely accepted by insurance companies active in Algeria, which announced their intention to adopt the Takaful insurance industry in the near future.
مقال
Keywords: Takaful insurance ; commercial insurance ; Salama Assurances Algérie ; the Algerian insurance sector